Meningkatkan Kemampuan Membaca Cepat - Annisa Rahmah; Hasna Salsabila (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The era of globalization demands the ability to read quickly as a crucial skill in facing the rapid growth of information. Speed reading is not just about speed, but also maintaining understanding of the reading content. This journal reviews the concept of speed reading, inhibiting factors, benefits, and strategies for increasing reading speed. The research method used is a qualitative approach with a focus on data collection and analysis. The results show that speed reading involves speed without compromising content understanding. Inhibitory factors involve vocalization, lip movements, head movements, finger pointing, regression, and subvocalization. Strategies to overcome inhibition include reducing physical movements, minimizing vocalizations, and strengthening self-confidence. The goals of speed reading involve efficiency in getting a general impression, finding specific information, and saving time. Increasing reading speed can be achieved through applying methods, focusing on relevant aspects, and avoiding inhibiting habits. This journal presents a comprehensive view to help individuals optimize their speed reading skills.